The slope-intercept form is <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>m</mi><mi>x</mi><mo>+</mo><mi>b</mi></mstyle></math> , where <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> is the slope and <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> is the y-intercept.

Reorder terms.

Find the values of <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> and <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> using the form <math><mstyle displaystyle="true"><mi>y</mi><mo>=</mo><mi>m</mi><mi>x</mi><mo>+</mo><mi>b</mi></mstyle></math> .

The slope of the line is the value of <math><mstyle displaystyle="true"><mi>m</mi></mstyle></math> , and the y-intercept is the value of <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> .

Slope: <math><mstyle displaystyle="true"><mfrac><mrow><mn>3</mn></mrow><mrow><mn>2</mn></mrow></mfrac></mstyle></math>

y-intercept: <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mo>-</mo><mfrac><mrow><mn>1</mn></mrow><mrow><mn>8</mn></mrow></mfrac><mo>)</mo></mrow></mstyle></math>

Slope: <math><mstyle displaystyle="true"><mfrac><mrow><mn>3</mn></mrow><mrow><mn>2</mn></mrow></mfrac></mstyle></math>

y-intercept: <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mo>-</mo><mfrac><mrow><mn>1</mn></mrow><mrow><mn>8</mn></mrow></mfrac><mo>)</mo></mrow></mstyle></math>

Find the x-intercept.

To find the x-intercept(s), substitute in <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> for <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> and solve for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> .

Solve the equation.

Rewrite the equation as <math><mstyle displaystyle="true"><mfrac><mrow><mn>3</mn><mi>x</mi></mrow><mrow><mn>2</mn></mrow></mfrac><mo>-</mo><mfrac><mrow><mn>1</mn></mrow><mrow><mn>8</mn></mrow></mfrac><mo>=</mo><mn>0</mn></mstyle></math> .

Add <math><mstyle displaystyle="true"><mfrac><mrow><mn>1</mn></mrow><mrow><mn>8</mn></mrow></mfrac></mstyle></math> to both sides of the equation.

Multiply both sides of the equation by <math><mstyle displaystyle="true"><mfrac><mrow><mn>2</mn></mrow><mrow><mn>3</mn></mrow></mfrac></mstyle></math> .

Simplify both sides of the equation.

Simplify <math><mstyle displaystyle="true"><mfrac><mrow><mn>2</mn></mrow><mrow><mn>3</mn></mrow></mfrac><mo>⋅</mo><mfrac><mrow><mn>3</mn><mi>x</mi></mrow><mrow><mn>2</mn></mrow></mfrac></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>3</mn><mi>x</mi></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Simplify <math><mstyle displaystyle="true"><mfrac><mrow><mn>2</mn></mrow><mrow><mn>3</mn></mrow></mfrac><mo>⋅</mo><mfrac><mrow><mn>1</mn></mrow><mrow><mn>8</mn></mrow></mfrac></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>8</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Multiply <math><mstyle displaystyle="true"><mfrac><mrow><mn>1</mn></mrow><mrow><mn>3</mn></mrow></mfrac></mstyle></math> and <math><mstyle displaystyle="true"><mfrac><mrow><mn>1</mn></mrow><mrow><mn>4</mn></mrow></mfrac></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>4</mn></mstyle></math> .

x-intercept(s) in point form.

x-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mfrac><mrow><mn>1</mn></mrow><mrow><mn>12</mn></mrow></mfrac><mo>,</mo><mn>0</mn><mo>)</mo></mrow></mstyle></math>

x-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mfrac><mrow><mn>1</mn></mrow><mrow><mn>12</mn></mrow></mfrac><mo>,</mo><mn>0</mn><mo>)</mo></mrow></mstyle></math>

Find the y-intercept.

To find the y-intercept(s), substitute in <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> for <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and solve for <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> .

Solve the equation.

Remove parentheses.

Simplify <math><mstyle displaystyle="true"><mfrac><mrow><mn>3</mn><mrow><mo>(</mo><mn>0</mn><mo>)</mo></mrow></mrow><mrow><mn>2</mn></mrow></mfrac><mo>-</mo><mfrac><mrow><mn>1</mn></mrow><mrow><mn>8</mn></mrow></mfrac></mstyle></math> .

Multiply <math><mstyle displaystyle="true"><mn>3</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

Divide <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> by <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> .

Subtract <math><mstyle displaystyle="true"><mfrac><mrow><mn>1</mn></mrow><mrow><mn>8</mn></mrow></mfrac></mstyle></math> from <math><mstyle displaystyle="true"><mn>0</mn></mstyle></math> .

y-intercept(s) in point form.

y-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mo>-</mo><mfrac><mrow><mn>1</mn></mrow><mrow><mn>8</mn></mrow></mfrac><mo>)</mo></mrow></mstyle></math>

y-intercept(s): <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mo>-</mo><mfrac><mrow><mn>1</mn></mrow><mrow><mn>8</mn></mrow></mfrac><mo>)</mo></mrow></mstyle></math>

Create a table of the <math><mstyle displaystyle="true"><mi>x</mi></mstyle></math> and <math><mstyle displaystyle="true"><mi>y</mi></mstyle></math> values.

Graph the line using the slope and the y-intercept, or the points.

Slope: <math><mstyle displaystyle="true"><mfrac><mrow><mn>3</mn></mrow><mrow><mn>2</mn></mrow></mfrac></mstyle></math>

y-intercept: <math><mstyle displaystyle="true"><mrow><mo>(</mo><mn>0</mn><mo>,</mo><mo>-</mo><mfrac><mrow><mn>1</mn></mrow><mrow><mn>8</mn></mrow></mfrac><mo>)</mo></mrow></mstyle></math>

Do you know how to Graph y=3/2x-1/8? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.

Name | one billion four hundred fifty-five million six hundred thirty-two thousand three hundred ninety-seven |
---|

- 1455632397 has 8 divisors, whose sum is
**1513159200** - The reverse of 1455632397 is
**7932365541** - Previous prime number is
**419**

- Is Prime? no
- Number parity odd
- Number length 10
- Sum of Digits 45
- Digital Root 9

Name | one billion nine hundred fifty-four million nine hundred thirty-four thousand one hundred forty |
---|

- 1954934140 has 16 divisors, whose sum is
**5278322232** - The reverse of 1954934140 is
**0414394591** - Previous prime number is
**5**

- Is Prime? no
- Number parity even
- Number length 10
- Sum of Digits 40
- Digital Root 4

Name | two billion twelve million six thousand two hundred thirty |
---|

- 2012006230 has 32 divisors, whose sum is
**3903026400** - The reverse of 2012006230 is
**0326002102** - Previous prime number is
**9619**

- Is Prime? no
- Number parity even
- Number length 10
- Sum of Digits 16
- Digital Root 7